2021
DOI: 10.4103/jehp.jehp_442_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice toward road safety regulations among college students in Telangana state

Abstract: BACKGROUND: Road traffic continues to be a major developmental issue and a public health concern. Road accidents in India kill almost 1.5 lakh people annually, and India accounts for almost 11% of the accident-related deaths in the world. Prevention of road traffic accidents is very crucial by creating awareness and taking proper measures toward road safety. AIMS: The aims of this study were to assess the knowledge about road safety regulations and to assess the attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…24 It is important for health systems to examine the needs and temporal and spatial conditions of the participants before the educational interventions. 25,26 The results of our study showed that the level of COVID-19 knowledge differed by socio-demographic factors, which could make them more vulnerable to the pandemic. This result coincides with those of other similar studies performed among public and healthcare professionals in various studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…24 It is important for health systems to examine the needs and temporal and spatial conditions of the participants before the educational interventions. 25,26 The results of our study showed that the level of COVID-19 knowledge differed by socio-demographic factors, which could make them more vulnerable to the pandemic. This result coincides with those of other similar studies performed among public and healthcare professionals in various studies.…”
Section: Discussionmentioning
confidence: 83%
“…24 It is important for health systems to examine the needs and temporal and spatial conditions of the participants before the educational interventions. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…This is of concern as, despite legislation promoting safe driving in these countries, the practiceknowledge gap amongst drivers contribute to high crash and road injury rates in LMICs. (Anebonam et al, 2019;Chen, 2010;Chen et al, 2016;Damsere-Derry et al, 2017;Jothula and Sreeharshika, 2021;Mohamad et al, 2019;Ngueutsa and Kouabenan, 2017;Staton et al, 2016) Research is needed to understand this gap and the factors surrounding how drivers in LMICs interact with the road system. Nonetheless, the strengths of this review includes the breadth of different eye diseases and vision-related interventions on numerous different driving performance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Road accidents are multi-cause events that frequently result from many factors, including driver error, the state of the road, and the condition of the vehicle [24][25][26]. It entails significant financial consequences to fatalities, injuries, and lost potential revenue, as well as significant human suffering [27,28]. Methods and techniques for minimizing the risk of a person using the road network, being killed or seriously injured are referred to as road traffic safety [29].…”
Section: Introductionmentioning
confidence: 99%